1992
DOI: 10.1111/j.1751-1097.1992.tb02230.x
|View full text |Cite
|
Sign up to set email alerts
|

PHYTOCHROME EVOLUTION: A PHYLOGENETIC TREE WITH THE FIRST COMPLETE SEQUENCE OF PHYTOCHROME FROM A CRYPTOGAMIC PLANT: (Selaginella martensii SPRING)

Abstract: We have sequenced cDNA and genomic clones coding for phytochrome of the fern Selaginella. On the amino acid level, this phytochrome shares sequence homologies with phytochromes of higher plants which range between 62 (phytochrome B of Arabidopsis) and 55 (56)% [phytochrome C of Arabidopsis (Avena)]. Introns in the Selaginella gene are short and occupy positions known from phytochrome sequences of higher plants. A rooted phylogenetic tree based on mutation distances puts Selaginella phytochrome closest to the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…from phytochrome sequences in seed plants have been found in Selaginella (Hanelt et al 1992), Adiantum PHYl and 2 (K. Nozue et al, unpublished results), PHYCER2 and MESPHYlb (Lagarias et al 1995), but another two and eight introns were found in PHYCER2 and MESPHYlb, respectively. Mougeotia may have the novel introns seen in Mesotaenium but not in Chara (Lagarias et al 1995).…”
Section: Gene Structurementioning
confidence: 99%
See 1 more Smart Citation
“…from phytochrome sequences in seed plants have been found in Selaginella (Hanelt et al 1992), Adiantum PHYl and 2 (K. Nozue et al, unpublished results), PHYCER2 and MESPHYlb (Lagarias et al 1995), but another two and eight introns were found in PHYCER2 and MESPHYlb, respectively. Mougeotia may have the novel introns seen in Mesotaenium but not in Chara (Lagarias et al 1995).…”
Section: Gene Structurementioning
confidence: 99%
“…Wbile four genes have been found in Anemia, in Adiantum capillus-veneris three genes {Adiantum PHYl-3) have been cloned from a genomic library and have also been sequenced as cDNAs (Okamoto et al 1993 (Hanelt et al 1992), but the gene family size is unknown. Other partial fern phytochrome sequences have been reported from Dryopteris filix-mas (Maucher, Scheuerlein & Schraudolf 1992), Equisetum and Marsilea (Kolukisaoglu et al 1995) as genomic PCR products.…”
Section: Gene Family and Molecular Speciesmentioning
confidence: 99%
“…2) establishes Physcomitrella phytochrome as a distantly b-type-related phytochrome or more precisely as a member of the lower plant phytochrome family. Numerous members of this family are known through chromophore-spanning PCR fragments which allow their ordering [4]. However, a- • Ara C (43.4) Fig.…”
Section: Fig 1 (Continued)mentioning
confidence: 99%
“…Because all lower plant phytochrome sequences (from cDNA as well as from genomic DNA) were isolated without any bias towards a certain type, it appears up to now that lower plants only harbour a sole type of phytochrome in contrast to higher plants where the evolutionary clock for phytochrome (a-, b-, and c-type Table I Per cent amino acid identity of pairs of complete phytochrome sequences (A) and distance scores (B) as computed and used by the TREE program (see [14]) of the GCG-package provided by the DKFZ (Deutsches Krebsforschungszentrum) database, Heidelberg The sequences used were Oryza a [15] and b [16], Arabidopsis a, b and c [17] and Selaginella [4]. (The respective EMBL accession numbers are X14172, X57563, X17341, X17342, X17343 and X61458.)…”
Section: Fig 1 (Continued)mentioning
confidence: 99%
See 1 more Smart Citation